2017
DOI: 10.18632/oncotarget.15781
|View full text |Cite
|
Sign up to set email alerts
|

MiR-519d impedes cisplatin-resistance in breast cancer stem cells by down-regulating the expression of MCL-1

Abstract: Cancer stem cells are considered as the cell population which is responsible for chemoresistance and treatment failure in breast cancer patients. Therefore, it is urgent to explore the mechanism by which cancer stem cells survive under the treatment of chemotherapeutic drugs such as cisplatin. In this paper, we demonstrated significant decrease of miR-519d in breast cancer stem cells by quantitative RT-PCR analysis. Furthermore, we found the enforced expression of miR-519d in T-47D-cancer stem cells significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 36 publications
0
40
0
Order By: Relevance
“…NDRG2 was introduced into SW620 cells, after which the cell cycle arrest was observed to arrest at G1/S phase [37] Cisplatin is the most common platinum-based chemotherapy drug. Its action mechanism is DNA crosslinking, so its tumor-suppressive activity is broad-spectrum and non-cell cycle-specific, leading to the inhibition of DNA replication and transcription and induction of tumor cell apoptosis [42,43]. Although cisplatin has been considered an effective agent for ovarian cancer treatment, the acquisition and development of drug resistance has emerged as a primary obstacle to its wide clinical application [44].…”
Section: Discussionmentioning
confidence: 99%
“…NDRG2 was introduced into SW620 cells, after which the cell cycle arrest was observed to arrest at G1/S phase [37] Cisplatin is the most common platinum-based chemotherapy drug. Its action mechanism is DNA crosslinking, so its tumor-suppressive activity is broad-spectrum and non-cell cycle-specific, leading to the inhibition of DNA replication and transcription and induction of tumor cell apoptosis [42,43]. Although cisplatin has been considered an effective agent for ovarian cancer treatment, the acquisition and development of drug resistance has emerged as a primary obstacle to its wide clinical application [44].…”
Section: Discussionmentioning
confidence: 99%
“…Among these proteins, we observed that the expression of MCL-1, which is an anti-apoptotic Bcl-2 family protein [26], was clearly increased in γδ T cell-resistant CD133 + A549 and PC9 cells (Fig. 3B).…”
Section: Imperatorin Sensitizes Cd133 + Lung Cancer Cells To γδ T Celmentioning
confidence: 95%
“…Recently, reduced expression of miR-519d was detected in BCSCs, and induced upregulated expression of miR-519d in cancer stem cells has been shown to sensitize towards chemotherapeutic drug cisplatin through activation of the mitochondrial apoptotic pathway. As a result, this significantly increased their sensitivity to cisplatin through MCL-1, a member of the proapoptotic Bcl-2 family, a dependent mitochondrial pathway in BCSCs [90].…”
Section: Breast Cancermentioning
confidence: 99%